COMMUNICATION, INTERACTION AND MANAGEMENT IN A CLASSROOM - Gafforova , Zarnigor Abdumumin qizi (Innovative Development in Educational Activities, 2023)
This article deals with the main activities such as communication, interaction and management in a classroom effective education refers to the degree to which schools are successful in accomplishing their educational objectives. This definition concentrates on the responsibility of the teacher and relates the use of classroom management strategies to multiple learning goals for students. Following this definition, effective classroom management skills seem to focus on preventive rather than reactive classroom management procedures. It is increasingly characterized by student-centered approaches to learning as opposed to teacher-centered, with a large emphasis on students’ metacognitive skills and cooperative learning.